Mental health status following severe sulfur mustard exposure: a long‐term study of Iranian war survivors. (5th August 2016) - Khateri, Shahriar; Soroush, Mohammadreza; Mokhber, Naghmeh; Sedighimoghaddam, Mohammadreza; Modirian, Ehsan; Mousavi, Batool; Mousavi, Seyed Javad; Hosseini, Maryam
Abstract: Introduction: This study aimed to describe the mental health status of sulfur mustard–exposed survivors suffering from severe respiratory and ophthalmological problems. Methods: Out of 450 invited Iran‐Iraq War survivors of sulfur mustard exposure with severe symptoms, 350 participated in this cross‐sectional study. Mental health status was assessed using the Diagnostic and Statistical Manual of Mental Disorders, fourth edition, criteria. Fisher exact test, Pearson chi‐square test, and chi‐square test were used to assess any relationship, and the independent‐sample t test was employed to compare differences between the veterans with ocular and pulmonary injuries. Results: There were 60.9% ( n = 213) survivors who suffered from mental disorders. Among them, 39.7% ( n = 139) were previously untreated and required the initiation of psychiatric treatment. The prevalence of anxiety and mood disorders among all survivors was 40.6% ( n = 142) and 32.0% ( n = 112), respectively. The most common anxiety and mood disorders were posttraumatic stress disorder (32.9%, n = 115) and major depressive disorder (22.3%, n = 78), respectively. Psychiatric disorders were more prevalent in cases with severe pulmonary chemical injury than in subjects with severe ophthalmologic chemical injury. Significant relationships were found between the types of psychiatric disorders and age, education, and occupation ( P < .05). Conclusion: The psychiatric morbidity in the chemically injured populations was remarkable and significantly different between the populations. The prevalence of mental illness in these groups highlights the need for the appropriate provision of mental health services.